Conceptualizing the Effect of CSR Activities on Affective Commitment and Corporate Performance - Alsamawi, Mohamed Abdulwali Ali; Mohd Ridzuan, Darun; Panigrahi, Shrikant (Institute of Research and Journals (IRAJ), 2018)
This paper provides a conceptual model that investigates the effect of Corporate Social Responsibilities (CSR)on affective commitment and corporate performance. Although the social and political issues are the root cause of the threat to sustainability development in the world, only corporations have the three essential components, namely resources, global reach and motivation, in order to achieve sustainability. Under competitive pressures, managers need to take into consideration the effect of organizational actions including corporate responsibility in order to retain valuable and non substituable human resources. The main purpose of this study is to increase corporate performance together with employee’s commitment towards the organization. From the economic distress and social challenges that Yemen is facing, it is very important to understand the complex connection and interdependence of CSR activities. Corporate can achieve long term growth followed with maintaining effective CSR activities and achieving corporate reputation. This study contributes to the literature of corporate communication to gain public legitimacy and corporate governance and develop a CSR model that explores critical dimensions in management of corporate culture in Yemen Oil industry. Keywords - Corporate social responsibilities, corporate culture, affective commitment, Yemen.